Travel Geography / Second Edition - Burton Rosemary (Pitman Publishing, 1995)
An essential introduction to the tourist regions of the world for all travel and tourism students. Preface, Introduction, World Geographical Resources for Tourism, The Use of Geographical Resources for Tourism, General Patterns of World Tourism, Patterns of Tourism in the World's Regions, Europe, Africa and the Middle East, The Americas, Asia and the Pacific Region, Conclusions, Index.